Preparation, Characterization, and Determination of Immunological Activities of Transfer Factor Specific to Human Sperm Antigen. (28th December 2012) - Zhou, Jianwei; Kong, Cui; Yuan, Zhaohong; Luo, Junmin; Ma, Rui; Yu, Jiang; Cao, Jinghe
Abstract : Objective. The objective of this study was to prepare, characterize, and determine immunological activities of specific transfer factor (STF) specific to human sperm antigen (HSA) for the preparation of antisperm contraceptive vaccine that can be used as an immunocontraceptive. Methods. HSA-STF was prepared using the spleens of rabbits vaccinated with HSA. The specific immunological activities were examined by lymphocyte proliferation test (LPT), leukocyte adhesion inhibition test (LAIT), and by determining the concentrations of IL-4, γ -IFN, and IL-21. HSA-STF was a helveolous substance, having a pH value of 7.0 ± 0.4 and UV absorption maxima at 258 ± 6 nm. It contained seventeen amino acids; glycine and glutamic acids were the highest in terms of concentrations (38.8 μ g/mL and 36.3 μ g/mL, resp.). Results. The concentration of polypeptide was 2.34 ± 0.31 mg/mL, and ribose was 0.717 ± 0.043 mg/mL. The stimulation index for lymphocyte proliferation test was 1.84, and the leukocyte adhesion inhibition rate was 37.7%. There was a statistically significant difference between the cultural lymphocytes with HSA-STF and non-HSA-STF for γ -IFN and IL-21 (P < 0.05 ), but there was no statistical significance for IL-4 (P > 0.05 ). Conclusion. HSA-STF was prepared and characterized successfully. It had immunological activity which could transfer the immune response specific to HSA and prove to be a potential candidate for the development of male immunocontraceptive agents.